Secretory overexpression of CGTase gene from bacillus sp. G1 in escherichia coli - Lo, Po Kim; Md. Illias, Rosli; Hassan, Osman; Mahadi, Nor Muhammad; Ahmad, Arshad (2005)
Cyclodextrin glucanotransferase (CGTases) catalyze the degradation of starch and maltodextrin to form cyclodextrins (CDs). CDs have various applications in food industry, cosmetic, pharmaceutical, toiletries, agrochemical industries and analytical chemistry. Overexpression of recombinant CGTase in intracellular E. coli expression system faces several problems especially the low expression level of recombinant CGTase and the formation of inclusion bodies. Low expression level is mainly due to the toxicity of accumulated recombinant protein that was expressed in the cytoplasm of E. coli, finally caused the cell death. Secretory E. coli overexpression system provides a promising solution to overcome this problem. The objective of this research is to overexpress the recombinant CGTase extracellularly in E. coli expression system. Preliminary studies show that co-expressing both CGTase and bacteriocin release protein (BRP) genes able to obtain the extracellular recombinant CGTase. The CGTase gene was amplified using polymerase chain reaction (PCR) method. The purified PCR fragment was cloned into pWH 1520 shuttle vector and transformed into E. coli that harbouring pJL3-BRP gene. The CGTase gene is regulated by xylA promoter and is induced by xylose; meanwhile the BRP gene is regulated by lac promoter and is induced by IPTG. The secretion pathway involves the permeabilization of the cell envelope that was activated by BRP and the release of bacteriocin molecules is accompanied by the release of the recombinant CGTase. The expression of extracellular recombinant CGTase at 37Â°C achieved 34.17 U/ml after 24 hours induction, with 0.5 mM xylose and 40Î¼M IPTG as inducers.